INTEGRASI PERMODELAN ENERGI-LINGKUNGAN DAN LONG RANGE ENERGY ALTERNATIVES PLANNING SYSTEM (LEAP): Kasus Indonesia - Jaka Aminata (Jurnal Dinamika Ekonomi & Bisnis, 2005)
AbstractThe Long-Range Energy Alternatives Planning System (LEAP) is a scenario-based energy environment modeling tool. LEAP as a database, it provides a comprehensive system for maintaining  energy information; as a forecasting   tool, it enables the user to make projections of energy supply and demand over a long-term planning horizan; as a policy analysis tool, it simulates and assesses the effects - physical, economic, and environmental of alternative energy programs, investments, and actions. Its scenarios are  based on comprehensive  accounting  of how energy is consumed, converted and produced  in a given region or economy under a range of alternative assumptions on population, economic development, technology, price and so on. With itsflexible data structures, LEAP allows for analysis as rich in technological specification and end-use detail as the user chooses. In this research, researcher put Indonesian case as "an intellectual exercise". However, LEAP has wide variety of projects, programs, technologies and other energy initiatives, and arrives at strategies that best address environmental and energy problems. Keywords: LEAP - energy demand - problem  tree - demand model -projection  - data structures